Pregnancy-associated breast cancer: course, diagnosis and treatment - I. A. Salov; T. A. Basova; Yu. V. Mikhailova; I. I. Frolova (Акушерство, гинекология и репродукция, 2024)
Pregnancy-associated breast cancer (ВС) is a rare pathology in the practice of an obstetrician-gynecologist and oncologist, which diagnostics is coupled to certain difficulties. The joint efforts of specialists to solve this issue taking into account current diagnostic and therapeutic opportunities are aimed at achieving a positive outcome. A clinical case of invasive hormone-dependent ВС T4bN3aM0, IIIC associated with pregnancy presented here is to outline a typical scenario of the following disease course: tumor manifestation in the second trimester, mastitis-like form, late diagnostics. The latter may result from low oncological alertness towards pregnant women under the age of 40 years old due to the rarity of such pathology. The proper decision-making of drug therapy algorithm according to the verified tumor histological variant and immunohistochemical status along with surgical treatment allowed not only to achieve tumor regression, give birth to a healthy full-term baby, but also gave a chance for survival despite late-onset treatment. To avoid advanced disease progression, it is advisable to recommend ultrasound breast examination in the first trimester for pregnant women over 35 years of age.